Upaya Penanggulangan Covid-19 Dalam Keluarga Civitas Akademika Universitas Nurul Jadid - Hafifah, Vivin Nur; Badriah, Septi Nur; Malasari, Putri Nur (Jurnal Keperawatan Profesional, 2021)
Abstract. Covid-19 is a disease that attacks the respiratory system, symptoms include runny nose, sore throat, cough and fever. And in some people the symptoms can be more severe and cause pneumonia or difficulty breathing, a small number of these cases lead to death. This study aims to measure the efforts to deal with Covid-19 in the academic family of Nurul Jadid Probolinggo University. This type of research is qualitative with a descriptive approach. data collection on February 2, 2021 after obtaining approval from the Institute for Publishing, Research and Community Service (LP3M). Participants involved in the research were 8 people including 3 health faculty lecturers, 2 engineering faculty lecturers, 2 Islamic religion faculty lecturers and 2 education staff. The selection of participants from the population used a purposive sampling approach with the criteria being on campus when the research was carried out. The consent of the participants to be involved in the study was proven by signing the informed consent. Data collection was carried out through structured interviews using instruments in the form of new interviews containing questions about efforts to tackle Covid-19. The interview process was carried out by applying health protocols such as wearing masks, physical distancing, and washing hands before and after the interview. The data obtained were analyzed using the triangulation method of data sources to identify the categories, sub-themes, and themes of the participants' experiences. categories that have meanings are arranged to form sub-themes, then sub-themes that contain similar meanings as research themes. Data analysis was performed manually using thematic analysis methods. The results of his research show that the family of the Nurul Jadid University academic community has made efforts to tackle Covid-19. The conclusion is that the family of the academic community has made efforts to tackle Covid-19, in the form of wearing a mask while working, maintaining distance, washing hands (using a hand sanitizer), increasing immunity, applying the correct cough ethics, changing clothes or showering when you get home, controlling comorbidities and cleaning routinely objects that are often handled with disinfectants because they are aware that the Covid-19 disease is very dangerous and can die in a community.